Conservation of plant genetic resources and prospects of cryopreservation - Panis, Bart (2023)
Invited speaker at Phytofactories 2023 international conference on Plant Molecular Farming, 7-9 June 2023 Luxembourg City Parc Belle Vue - Parc Plaza